FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN STROKE - Yuliany Rahmawati, Endah; Masdah, Siti; Sakke Tira, Deviarbi; Awal, Muhammad; Arpandjam'an, Arpandjam'an (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Stroke is one of the neurological disorders that is also an acute vascular injury to the brain. Based on observations on October 1, 2022, of 7 stroke patients in the inpatient room of Awal Bros Panam Hospital (RSAB Panam), 5 patients (71%) had a history of hypertension and 2 patients (29%) had a history of diabetes mellitus. 4 patients (57%) were male and 3 patients (43%) were female. 5 patients (71%) had an age of >40 years while 2 patients (29%) were at the age of 25-40 years. 4 patients (57%) had a history of smoking and 3 patients (43%) did not have a history of smoking but were exposed to smokers (passive smokers). 3 patients (43%) were in the obese weight category, 3 patients (43%) were in the normal weight category and 1 patient (14%) was in the underweight category. The purpose of the study was to determine the factors associated with the incidence of stroke. This type of research uses quantitative research with a cross sectional design. The sample amounted to 30 people with sampling techniques using accidental sampling. The results showed there was a relationship between age (p value: 0.001), history of hypertension (p value: 0.027). It is recommended that health workers conduct counseling or provide information to the public about secondary prevention efforts (healthy lifestyle, risk factor control) can be done directly in the form of counseling or indirectly in the form of media such as advertisements, posters / brochures. Keywords: Hypertension, Gender, Stroke